CALCIUM OXALATE WITH UROLITHIASIS SICK PATIENTS NATIONAL FROM FOOD STRUCTURED RATION ON THE BASIS OF TAKE VISITED METAPHYLAXIS DURING DAILY IN THE URINE CALCIUM DIVORCE INDICATOR (E Global Congress, 2025)
Urinary stone disease (UST) is one of the most common diseases in the world. According to several studies, the global prevalence of UST is 3.5-9.6%. Urolithiasis is the third most common urological disease and accounts for 30-40%. When examining studies on a country-by-country basis, the prevalence of UST is 5-10% in European countries, 7-15% in the USA, 20% in Arab countries, and 1-5% in Asian countries. In calcium oxalate urolithiasis, the presence of crystalluria in the urine indicates the presence of general and specific metabolic disorders, which are characteristic of the disease.